Acceleration And Deceleration Of Breakage Rates In Batch Grinding - Raj K. Rajamani (Society for Mining, Metallurgy & Exploration, 1991)
In ball milling the rates of breakage vary primarily with the size distribution of powder in the mill. In wet grinding viscosity of the slurry varies continually as size distribution changes and hence the breakage rates change. In this study a simpler estimation scheme is used to determine breakage rates in batch grinding. Using an approximate solution to the batch grinding equation, acceleration and deceleration of breakage rates of all individual size classes is determined when the grinding environment is varied. Experimental results with limestone and copper ore show time-dependent breakage rates under both dry and wet grinding conditions. In general the breakage rates increase for coarse sizes and decrease for fine sizes with increase in the fines present in the mill. Such variations have strong implications in closed-circuit grinding.